Access to HIV Prevention Services for Injecting Drug Users in Hai Phong, Vietnam: Qualitative Results - Ahmed, Tanvir; Stewart, Donald Edwin (International Journal of Medical and Health Sciences Research, 2014)
Background: To attain a deeper understanding of risk behaviour and service engagement among Injecting Drug Users (IDUs) in Hai Phong, Vietnam, we conducted a qualitative follow-up series of in-depth interviews. This paper presents the barriers and facilitative factors relating to prevention services. Methods: Fifteen semi-structured face-to-face interview with IDUs were conducted. Results: The participants are often satisfied with their current access to the HIV prevention services; however, they highlighted the issues for better engagement in the future. The qualitative findings document barriers as well as facilitative factors in accessing the services. Humane approach, pleasant experience, and free treatment facility are commonly cited facilitative factors. The frequently occurring barriers to accessing HIV prevention service include long distances between place of delivery and home, unavailability in local neighbourhoods and mismatched delivery time. Conclusion: Access to HIV prevention services needs to be strengthened according to the need of IDUs to limit the further spread of HIV epidemic.